Comparative Study of Economic Learning Outcomes Using Problem Based Learning and Project Based Learning Models by Considering Student Learning Activities - Saputra, Jaya; Rusman, Tedi; Suroto, Suroto; Rahmawati, Fanni (FKIP Universitas Lampung, 2024)
This study aims to explore the effectiveness of problem-based (PBL) and project-based (PjBL) learning models on students' economic learning outcomes with different learning activity levels. Using a quasi-experimental method with a 2x2 factorial design and a purposive sample of 67 students, data were collected through interviews, observations, documentation, tests, and experiments. Hypothesis testing was done with two-way ANOVA and t-test of two independent samples. The results showed no significant difference in economic learning outcomes between PBL and PjBL models. However, there was a significant difference between students with high and low learning activities. The average learning outcomes of students with high learning activities were better using PjBL, while students with low learning activities were better using PBL. There was no significant interaction between learning models and learning activities on economic learning outcomes. This research provides important insights for educators in choosing the appropriate learning model to improve economic learning outcomes.Keywords: Problem Based Leraning (PBL), Project Based Learning (PjBL), Learning Activity, Economic Learning OutcomesDOI: http://dx.doi.org/10.23960/E3J/v7i1.63-71